Design and evaluation of the production of 50,000 metric tonnes/year of methanol using pre-combustion carbon capture technology / Mohd Aizad Ahmad, Nur Afiffah Ahmad Raof and Zulkifli Abdul Rashid - Ahmad, Mohd Aizad; Ahmad Raof, Nur Afiffah; Abdul Rash, Zulkifli (Universiti Teknologi MARA Shah Alam, 2018)
Carbon dioxide (CO2) emission contributes largely to the increasing level of greenhouse gases in the atmosphere. Carbon capture and storage (CCS) and carbon capture utilisation (CCU) are evaluated as a fundamental technology that contributing to the reduction of CO2 emission. Thus, this study concerns about the design of 50,000 tonnes/year of methanol using pre-combustion CO2 capture technology. Aspen HYSYS version 8.8 was used as a tool for simulating the methanol production process. The simulation mainly covered the pre-combustion CO2 capture technology using Selexol method and methanol production plant from CO2 as raw material. The methanol plant electric capacity was evaluated based on the capacity of three coal-fired power stations in Malaysia. The CO2 was fed at 120 kPa and H2 at 101.3 kPa, into the methanol plant which resulted in 21.9% purity of methanol and water. The CO2 need to produce targeted 50, 000 tonne/year of methanol is 1500×104 kg/hr. The emission of CO2 by the Sultan Salahuddin Abdul Aziz Shah Power Station is 326 kg/hr which produce 0.09 kg/hr of methanol.